Analisis Pengelolaan Dana Bantuan Operasional Kesehatan (BOK) pada Puskesmas Kuala Bhee Kabupaten Aceh Barat - Ferdyan Ardhana; Irmawati Irmawati; Cut Fitrika Syawalina (AKUNTANSI 45, 2025)
This study aims to evaluate the management of the Health Operational Assistance Fund (BOK) at the Kuala Bhee Health Center, West Aceh Regency, during the period 2022 to 2024. The method used in this research is quantitative descriptive analysis, which is an approach used to describe data systematically, factually, and accurately based on actual conditions in the field, with the main focus on the management of BOK funds. The analysis was conducted using the effectiveness ratio. The results showed that the management of BOK funds at the Kuala Bhee Health Center has referred to the provisions of the Regulation of the Minister of Health of the Republic of Indonesia Number 18 of 2024, which includes the stages of planning, implementing activities, reporting, and monitoring and evaluation. The level of BOK budget realization in 2022 and 2024 was classified as effective because the percentage of realization was in the range of 90-100%. This indicates that the management of funds is carried out well, although there is still a large remaining budget. Meanwhile, in 2023, the budget realization rate was in the range of 80-90%, indicating that the management of funds in that year was quite effective.